2008
DOI: 10.1021/ol802218a
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Sequential Carbon−Carbon Bond Cleavage/Formation Producing Arylated Benzolactones

Abstract: 3-(2-Hydroxyphenyl)cyclobutanones react with aryl bromides in the presence of palladium catalysts to afford 4-arylmethyl-3,4-dihydrocoumarins in high yields through a sequence involving carbon-carbon bond cleavage and formation. In the case of the reaction with 2-(2-hydroxyphenyl)cyclobutanones, five- or seven-membered lactones were produced depending on the presence of an additional substituent at the 2-position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(13 citation statements)
references
References 20 publications
1
10
0
2
Order By: Relevance
“…Furthermore,a ldehyde 11 was not converted into 4aaunder the standard reaction conditions (Scheme 4b). These results indicate that apathway involving migratory insertion of the carbonyl group and b-hydride elimination was less likely, [15] which is in good agreement with the computational studies (see below). As depicted, no significant kinetic isotope effect (k H /k D = 0.96) was observed, suggesting that C À Hb ond cleavage was not involved in the rate-determining step (Scheme 4c).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore,a ldehyde 11 was not converted into 4aaunder the standard reaction conditions (Scheme 4b). These results indicate that apathway involving migratory insertion of the carbonyl group and b-hydride elimination was less likely, [15] which is in good agreement with the computational studies (see below). As depicted, no significant kinetic isotope effect (k H /k D = 0.96) was observed, suggesting that C À Hb ond cleavage was not involved in the rate-determining step (Scheme 4c).…”
supporting
confidence: 87%
“…Somewhat surprisingly,t he solvent seemed to have ap ronounced effect. Fore xample, when the reaction was carried out in PhCF 3 with triphenylphosphine or tri(furan-2-yl)phosphine as the ligand, negligible amounts of 4aa could be detected in the reaction mixture.I nc ontrast, with DMF as the solvent, product 4aa was isolated in 52 %a nd 65 %y ield, respectively,u nder otherwise identical conditions.S imilarly,t he use of other solvents afforded decreased yields of the product (entries [12][13][14][15]. As expected, strict control experiments demonstrated that all of the reaction components were crucial for the annulation to occur (entry 16).…”
mentioning
confidence: 61%
“…In 2008, Murakami and co-authors reported that they used 2-(2-hydroxyphenyl)cyclobutanones and aryl halogen as the substrates got a series of five-or seven-membered lactones in the presence of palladium catalysts (Scheme 13). 26 When using Pd(0)-P( t-Bu)3 as catalyst, cyclobutanone reacted with aryl iodide which gave seven-membered desire product in 79% yield.. In contrast, when using 2,2-disubstituted cyclobutanone as the substrate, it obtained five-membered benzolactones.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…261 Han and Lu obtained 3,4-disubstituted dihydrocoumarins 426a in excellent yields using substituted alkynals 424 in combination with ArB(OH) 2 425 in the presence of catalytic amounts of cationic palladium complexes. 262 They have also synthesized asymmetric dihydrocoumarins 426b using chiral bisphosphines as ligands, in good yields and high enantioselectivities (Scheme 108).…”
Section: Scheme 103mentioning
confidence: 99%